2005
DOI: 10.1253/circj.69.739
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nifekalant, a Class III Anti-Arrhythmic Agent, on Ca2+ Waves in Rat Intact Trabeculae

Abstract: S-551, a class III anti-arrhythmic agent, with a pyrimidinedione structure, inhibits the rapiddelayed rectifier K + currents (IKr) at therapeutic concentrations of 1-10 mol/L 1 and, furthermore, inhibits several other K + channels at concentrations above 10 mol/L. [2][3][4][5][6] The blocking of K + channels can prolong the duration of the action potential 4,7 and consequently prolong the myocardial refractory period, 4,[6][7][8][9] suggesting that the chief anti-arrhythmic action of nifekalant comes from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…These discrepancies may be due to differences in the hemodynamic load, chamber geometry, and cell-cell or cell matrix connectivity between these preparations. Therefore, to fill the gap between isolated myocytes and whole hearts , we used in this study multicellular ventricular muscle with the original cell-cell and cell-matrix connectivity (Sys et al, 1998) and measured the contractile properties with the proper load at the sarcomere length of 2.1 m (Miura et al, 1999;Hirose et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These discrepancies may be due to differences in the hemodynamic load, chamber geometry, and cell-cell or cell matrix connectivity between these preparations. Therefore, to fill the gap between isolated myocytes and whole hearts , we used in this study multicellular ventricular muscle with the original cell-cell and cell-matrix connectivity (Sys et al, 1998) and measured the contractile properties with the proper load at the sarcomere length of 2.1 m (Miura et al, 1999;Hirose et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The sarcomere length was measured using laser diffraction techniques (ter Keurs et al, 1980;Wakayama et al, 2005). Membrane potential was measured using ultracompliant glass microelectrodes, as described previously (Hirose et al, 2005). To estimate the duration of action potential, the time to 90% repolarization of the action potential (APD 90 ) was measured.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is suggested that nifekalant increased intracellular calcium concentration associated with the prolongation of action potential duration resulting in the increase of myocardial contraction. 13 …”
Section: Adverse Effectsmentioning
confidence: 99%